New Perspectives for an Intelligent Risk-Based Decision Support Framework for Asset Integrity Management. Means for Sustainable Asset Integrity Management in the Norwegian High-North. - Ilora, Obiora Nnamdi (UiT Norges arktiske universitet, 2018)
The Norwegian Arctic - Barents Sea, is attracting more oil and gas developments. The associated growth of assets will face heightened integrity issues considering the prevalent climatic and challenging operating conditions in the Arctic. This thesis focuses on identifying asset integrity management critical success factors which are often neglected but are the bed rock of asset integrity management. The knowledge of these critical success factors will be used to upgrade existing decision support system framework for asset integrity management for use in the Arctic - Barents Sea. Framework Objectives: 1. To assure higher degree of early detection and intervention for integrity issues. 2. To assure higher degree of risk predictability of mechanical integrity issues. Data and Risk Decision Management were proposed as the two Asset Integrity Management Critical Success factors which will bring about the desired improvement. Attention was given to data visualization approach in a way to aid smart risk communication and decision. Further research is necessary to improve methods for proactive risk identification and mitigation, aid development of performance indicators for proactive risk thresholds and improve the understanding of data quality and possible use as a performance indicator.